Anti-haecceitism and indiscernibility. - Roberts, Alexander (Analysis, 2024)
It is often presumed that anti-haecceitists are not committed to the identity of indiscernibles. However, I argue that anti-haecceitism implies a particularly strong thesis about when individuals are indiscernible which motivates the identity of indiscernibles. The argument is first sketched intuitively and then formalized in a system of higher-order modal logic.